Immigration and Distribution of Wages in Austria - Gerard Thomas Horvath (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
Using detailed micro data on earnings and employment, I analyze the effects of immigration on the wage distribution of native male workers in Austria. I find that immigration has heterogeneous effects on wages, differing by type of work as well as the wage level. While there are small , but insignificant, negative effects for blue collar workers at the lower end of the wage distribution there are positive effects on wages at higher percentiles. For white collar workers positive effects occur at most percentiles. The estimated effects of immigration are relatively small in size and not significant for most workers. Overall it seems that most of potentially adverse effects of immigration on natives' wages are offset by complementarities stemming from immigration of workers with different skill levels.
Keywords: J31; J61; 330; Immigration; Labor market; Wage distribution